In vivo evaluation of antinociceptive activities of 2-benzoyl-6-(3,4-dihydroxybenzylidene)cyclohexen-1-Ol and its possible mechanism of actions - Ahmad Azmi, Ahmad Farhan (2021)
The present study examined the potential antinociceptive activity of 2-benzoyl-6-(3,4-dihydroxybenzylidene)cyclohexene-1-ol (BDC) and its possible mechanism of actions in mice models. BDC, a novel synthetic curcuminoids was freshly prepared and used throughout this experiment. The experimental models were conducted using 6 male ICR mice per group and the one-way analysis of variance (ANOVA) was used to analysed the gathered data by running Tukey’s post hoc test with p < 0.05, p < 0.01 and p < 0.001 for statistically significant different. Based on toxicological studies, BDC showed a Lethal does 50 (LD50) greater than 2000 mg/kg sand categorized 5 according to Globally Harmonized System for the classification of chemicals. The oral administration of BDC at doses of 1-30 mg/kg followed by 7 days consecutive observation did not show any death occurrence or any signs of toxicity. The body weights, liver and kidneys, hematological and liver function parameters showed no sign of abnormality. The findings were further supported by the histopathological observations of the liver, kidney and spleen that demonstrated normal histological structure. The determination of the antinociceptive profiles of BDC were through acetic acid-induced abdominal writhing test and hot plate on mice. BDC shown significant inhibitory activity of pain and prolonged time latency on hot plate, suggesting the possible involvement of BDC in both peripheral and central systems of the pain pathway. The rota-rod evaluation confirmed that the antinociceptive effects of BDC were not associated to any non-specific sedative effects such as muscle relaxant or sedation. Further evaluation with formalin-induced paw licking test demonstrated that BDC interacts with opioid receptors in both phases. The study continued to demonstrate the ability of BDC to inhibit pain through the nitric oxide pathway inactivating a series of event involving the L-Arginine-NO-cGMP-K+-ATP channel pathways in the acetic acid-induced abdominal writhing test. BDC also showed interactions with two other receptors mainly the NMDA and TRPV1 receptors. Moreover, BDC interacts with other prominent receptors involved in antinociception including GABAergic, cholinergic, dopaminergic, noradrenergic, serotonergic and adenosinergic systems. The mechanism of action of BDC was further evaluated with the involvement of the Ca2+ activated potassium channels, eventually confirming the involvement of the small and large conductance calcium-gated K+ channels, voltage-gated K+ and ATP-gated K+ channels. The involvement of inflammatory mediators on BDC antinociceptive was evaluated using various inflammatory chemical mediators that act as inducers, mainly bradykinin, histamine, serotonin, substance P, phospholipase A2, prostaglandin E2 and arachidonic acid, of which BDC at all doses significantly suppressed inflammatory mediators-induced inflammation in all inflammatory chemical mediators-induced experiments. As a conclusion, BDC exerted antinociceptive activity by modulating the activation of various receptors, ion channels, L-arginine-nitric oxide-cGMP pathway and descending inhibitory pathways.